2021
DOI: 10.3389/fnut.2021.738281
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin–Zinc Complex Alleviates Inflammatory Responses and Hormone Profiles by Microbiome in Deoxynivalenol Induced Piglets

Abstract: This study aimed to investigate the beneficial effect of baicalin–zinc complex (BZN) on intestinal microorganisms in deoxynivalenol (DON)-challenged piglets and the association between intestinal microorganisms and host immunity and hormone secretion. Forty weaned piglets were randomly divided into four treatments with 10 piglets in each treatment: (1) control (Con) group (pigs fed basal diet); (2) DON group (pigs fed 4 mg DON/kg basal diet); (3) BZN group (pigs fed 0.5% BZN basal diet); and (4) DBZN group (pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In addition, the immune and inflammatory response is closely associated with intestinal barrier function [ 52 , 53 ]. sIgA, an immunoglobulin secreted by plasma cells of the intestinal mucosa, is a major effector of the intestinal mucosal immunity, which acts as the first defense line to prevent the colonization of pathogens in the intestinal mucosa and plays an important role in local anti-infection of the body [ 24 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the immune and inflammatory response is closely associated with intestinal barrier function [ 52 , 53 ]. sIgA, an immunoglobulin secreted by plasma cells of the intestinal mucosa, is a major effector of the intestinal mucosal immunity, which acts as the first defense line to prevent the colonization of pathogens in the intestinal mucosa and plays an important role in local anti-infection of the body [ 24 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has synthesized complexes of baicalin with a variety of metal ions, and activity studies have demonstrated that all of these metal complexes are significantly more active than baicalin. For example, baicalin–zinc 35 and baicalin–copper 36 can increase the diversity of intestinal flora in experimental animals and reduce inflammation; baicalin–vanadium( iv ) has good anti-mutagenic 37 and antioxidant effects; 38 SMMC-7721 cells are effectively inhibited by baicalin complexes containing La, Y, Ce, and other rare-earth elements; 22 and baicalin complexes with La, Y, Al, and Cu are effective inhibitors of a wide range of bacteria and fungi. 39,40 Evidence also shows that baicalin–Zn is effective at treating chronic gastric ulcers.…”
Section: Resultsmentioning
confidence: 99%
“…Zha et al. (2021) indicated that the baicalin–zinc complex (4 mg/kg DON and 0.5% baicalin zinc [BZN] basal diet) can alleviate the inflammatory response and modulate the secretion of hormones related to growth axis secretion in piglets.…”
Section: Don Biological Detoxification Methods and Nutritional Mitiga...mentioning
confidence: 99%
“…Savi et al (2022) demonstrated that MSNs incorporated with zinc oxide (MSNs-ZnO, 1.0 mg/mL) can affect the growth of F. graminearum and the production of DON. Zha et al (2021) indicated that the baicalin-zinc complex (4 mg/kg DON and 0.5% baicalin zinc [BZN] basal diet) can alleviate the inflammatory response and modulate the secretion of hormones related to growth axis secretion in piglets.…”
Section: Vitamins and Microelementsmentioning
confidence: 99%